Semi‐polar (112¯2)‐GaN templates grown on 100 mm trench‐patterned r‐plane sapphire. Issue 5 (20th March 2015) - Brunner, Frank; Edokam, Francis; Zeimer, Ute; John, Wilfred; Prasai, Deepak; Krüger, Olaf; Weyers, Markus
<x xml:space="preserve">Abstract</x> This report describes the successful realization of high‐quality semi‐polar <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjkz9dtj2" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />(112¯2)</alternatives> ‐GaN templates grown on 100 mm diameter r‐plane patterned sapphire. Trench patterning is accomplished by plasma etching using a slanted SiNx mask that is formed by a resist‐reflow process and subsequent dry etching. Epitaxial overgrowth by MOVPE is optimized with the aid of in situ monitoring to trace GaN coalescence behavior and surface morphology. Wafer curvature at growth temperature exceeds typical values of c‐oriented GaN, whereas room‐temperature bow is spherical and comparable to polar material. Morphological and structural properties compare well with published data on 2 in. substrates. Threading dislocation densities of about 2 × 108 cm−2 and basal stacking fault densities in the order of 1 × 103 cm−1 are deduced from cathodoluminescence studies. Low residual impurity concentrations ([O, Si] < 1 × 1017 cm−3) have been verified.